PP148 A Stakeholder-Informed Strategy For Effective Communication. (2019) - Elston, Lauren; Poole, Ruth Louise; Fraser, Barbara; Coldwell, Ian; Myles, Susan
Abstract : Introduction: Effective communication is vital for engaging stakeholders in health technology assessment (HTA), as well as the successful dissemination and adoption of HTA research and guidance. As a relatively new organization, Health Technology Wales (HTW) has an ideal opportunity to take an effective, strategic approach to communication and stakeholder engagement from the outset. Methods: HTW commissioned Pagoda Public Relations to develop an informed communications strategy and delivery framework. The strategy used OASIS methodology for public relations planning: Objectives, Audience insight, Strategy, Implementation, and Scoring (evaluation). Initial objectives were developed with input from the HTW team and members of the HTW Assessment Group and Appraisal Panel. Stakeholder insights were collected through an online survey and telephone interviews. These insights were used to inform the communications strategy and framework, outlining key audiences, key messages, communication objectives, methods, tactics, and evaluations. Results: Seven key objectives were identified, each of which were supported by recommended actions. These were underpinned by the key aims and messages reflecting how we will achieve these objectives. National Health Service boards, government, clinicians, the technology and research sector, patients, and the general public were identified as priority audiences. Various different communication channels and activities were identified, aimed at various audiences. These included the website, social media, traditional media, and exhibitions or workshops, as well as targeted e-mail dissemination of guidance. Evaluation of HTW communications will be aligned with the wider HTW evaluation strategy, and evidence will be recorded through OutNav software (Matter of Focus Ltd). Conclusions: HTW is committed to a strategic, effective approach to communication and engagement. We now have an audience-informed communications strategy and plan that outlines our key objectives, and how to achieve and evaluate these objectives. Successful implementation will raise awareness of and value in profile and outputs of HTW, both in Wales and internationally.